2020
DOI: 10.3390/ijms22010389
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Disorders Due to Limbic Encephalitis: Immunologic Aspect

Abstract: Limbic encephalitis (LE) is a rare cause of encephalitis presenting as an acute and subacute onset of neuropsychiatric manifestations, particularly with memory deficits and confusion as core features, along with seizure occurrence, movement disorders, or autonomic dysfunctions. LE is caused by neuronal antibodies targeting the cellular surface, synaptic, and intracellular antigens, which alter the synaptic transmission, especially in the limbic area. Immunologic mechanisms involve antibodies, complements, or T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 170 publications
1
14
0
3
Order By: Relevance
“…Hervorragende Zusammenfassungen des Kenntnisstands zu Art, Häufigkeit, Pathomechanismen und Therapie von Autoimmunenzephalitiden finden sich in [15,29]. Anwendungsorientierte Zusammenfassungen für den Kliniker finden sich in [2, 14,30,31,32,33], für Autoimmunenzephalitiden speziell bei älteren Patienten in [34,35].…”
Section: Hintergrundwissenunclassified
“…Hervorragende Zusammenfassungen des Kenntnisstands zu Art, Häufigkeit, Pathomechanismen und Therapie von Autoimmunenzephalitiden finden sich in [15,29]. Anwendungsorientierte Zusammenfassungen für den Kliniker finden sich in [2, 14,30,31,32,33], für Autoimmunenzephalitiden speziell bei älteren Patienten in [34,35].…”
Section: Hintergrundwissenunclassified
“…Local pathologic effects following antibody-antigen interaction include direct blockade of cell-surface channels and receptors and internalization of cell-surface receptors. The autoantibodies may also activate natural killer cells or the complement system and thus promote complement-mediated or cell-mediated cytotoxicity and subsequent neuronal death [ 16 ].…”
Section: Reviewmentioning
confidence: 99%
“…3,4 Other antibodies include anti-a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor antibodies, anti-gammaaminobutyric-acid B receptor antibodies and antibodies to other antigens present in the neuropil of the hippocampus and cerebellum. 5 However, previous studies reported that some patients presented with LE antibody-negative. 6,7 Limbic encephalitis includes a broad spectrum of clinical symptoms with subacute onset and it can cause persistent brain damage.…”
Section: Introductionmentioning
confidence: 98%